The Changing Face of Malignant Hyperthermia: Less Fulminant, More Insidious. Issue 4 (July 2015) - Heytens, L.; Forget, P.; Scholtès, J. L.; Veyckemans, F.
Modern anaesthetic techniques have resulted in the clinical presentation of malignant hyperthermia to be more often indolent and/or insidious than truly fulminant, as previously known in the anaesthetic community. We present four recently referred cases to illustrate this point: one late-onset case, two patients with slowly progressive hypercapnia as the sole sign and a fourth patient with postoperative myalgias and elevated creatine kinase. We also discuss the reasons for the shift in typical clinical presentation. The more insidious character of malignant hyperthermia is most likely due to the lower triggering potency of modern volatile anaesthetics, the mitigating effects of several intravenous drugs (neuromuscular blocking agents, alpha 2 adrenergic receptor agonists, beta-adrenergic blockade) or techniques (neuraxial anaesthesia) and the routine use of end-tidal CO2 monitoring leading to the early withdrawal of triggering drugs. Awareness among anaesthetists of this change in presentation is important since the clinical diagnosis is often more doubtful and, if corroborative evidence is not sought, the diagnosis may be delayed or missed altogether.